The Dollar and Gold: Which is the Safest Haven? COVID-19 Evidence - Bousbia Salah Rahima; Beggat Hanane; Debbar Abdelkerim (Economics and Business, 2023)
This paper examines the dynamic correlation between the US dollar and gold prices during the coronavirus pandemic to determine which of the two assets is a safer haven from an investor’s perspective. The research utilises methods of analysis and synthesis of theoretical knowledge from published articles, literature, and official statistics websites. Data covering the period from January 1, 2020 to May 26, 2021, were primarily collected from the latest versions of these websites. The study includes a quantitative analysis of variables, including the Johansen cointegration test, the Granger causality test, and the error correction model. Our empirical analysis reveals a long-term equilibrium relationship between the US dollar and gold price. There is a oneway inverse causality relationship between the dollar and gold price. The results indicate that gold can be considered the safest haven from the investors’ perspective.